Sustainable Supply Chain Practices at Packaging Company: Analysis of Huhtamaki Environmental Sustainability - Rahman, Md. Habibur (My University, 2026)
In global food and beverages supply chain, sustainability of packaging plays a signifi-cantly important role, since it influences the extent to which the raw materials, energy and water are consumed in production. Despite this importance, there is scarcity of longitudinal studies tracking the environmental performance of packaging manufacturers against its stated targets across multiple years. This thesis has addressed this gap. The research has selected Huhtamaki and its performance in environmental sustainability since the company is a key supplier of packaging across the globe. Secondary data design has been used and has analysed the Annual Report from 2022 to 2025. The environmental dimensions examined in this research include greenhouse gas (GHG) emissions, renewable energy use, raw materials’ sustainability and waste management. The analysis addresses the question: To what extent has Huhtamaki demonstrated measurable and consistent improvement in environmental sustainability across its supply chain operations between 2022 and 2025? The findings show that environmental performance of Huhtamaki has improved consistently across all four dimensions during the studied years. Scope 1 and Scope 2, combined, GHG emissions reduced by approximately 40 percent against stated baseline by 2024, and this was largely driven using renewable electricity to 60.9 percent in 2025 from 24.9 percent in 2022. Landfill waste also reduced to 4.7 percent from 10 percent and recycled or renewable materials’ share rose to 68 percent from 65.8 percent. Furthermore, validation was received by Huhtamaki for Science Based Targets Initiatives, since it upgraded to 1.5°C emissions target, and for its sustainability performance was awarded EcoVadis Gold Medal. The research based on its findings concluded that Huhtamaki has demonstrated consistent environmental progress within the global packaging supply chain, but still there are some prominent gaps in Scope 3 emissions and adoption of circular packaging. This requires coordinated action across the entire supply chain.
Keywords: supply chains; sustainable development; emissions; recycling; waste management; logistics; circular economy; environmental effects; eco-efficiency; green economy; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management